Forest gardens - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Increasing population pressure has almost invariably led to clearance of forest and the substitution of a wide variety of mostly perennial species by mono cultures of a few annual staple crops - cereals, tubers, pulses and vegetables. The assumption...